ვარლამ ჩერქეზიშვილი – სახელმწიფოს მშენებელი ანარქისტი - შველიძე, დიმიტრი (მერიდიანი, 2015)
After abolishment of the Russian monarchy, Varlam Cherkezishvili was back from long-term emigration. First he went to Russia, then – Georgia. August-November of 1917 is a period of his involvement in construction of national state institutions. Documents show that Varlam Cherkezishvili was extremely active in national interparty council. He was negotiating with the Russian political and military leaders for creation of national military units, he also took part in organizing of I national congress, etc. All the documents show him as Ivane Cherkezishvili from socialist revolutionary party. This way he tried to hide himself. Indeed, as anarchist he felt uncomfortable taking part in state building.
VARLAM CHERKEZISHVILI – STATE BUILDER ANARCHIST
https://geohistory.humanities.tsu.ge/ge/procedings/83-shromebi/163-shromebi-9.html
Keywords: ანარქიზმი; პარტიები; იდეოლოგიები